Cutting brittle rods using elastic wave propagation - Šidlof P.; Pustka M.; Braier Z. (Applied and Computational Mechanics, 2021)
For the sake of intended industrial applications, the stress wave propagation in thin rods of brittle material is measured and explored. Based on the known theory of a non-dispersive wave propagation in rods, a numerically efficient method for the calculation of wave propagation and reflection is presented. The effects of an impact applied to a thin rod are tested and measured on a test bench. The results of these measurements carried out on glass capillary tubes are successfully compared with theoretical results and they confirm the possibility of brittle rod cutting by means of elastic waves with the required fracture surface quality.